The Role of Lysophosphatidic Acid in Neuropsychiatric and Neurodegenerative Disorders - Simona Dedoni; Chiara Camoglio; Carlotta Siddi; Maria Scherma; Walter Fratta; Paola Fadda (Future Pharmacology, 2024)
Individuals suffering from diverse neuropsychiatric and neurodegenerative disorders often have comparable symptoms, which may underline the implication of shared hereditary influences and the same biological processes. Lysophosphatidic acid (LPA) is a bioactive phospholipid and a crucial regulator of the development of adult neuronal systems; hence, it may play an important role in the onset of certain diseases such as Alzheimer’s, Parkinson’s disease, and schizophrenia. During development, LPA signaling regulates many cellular processes such as proliferation, survival, migration, differentiation, cytoskeleton reorganization, and DNA synthesis. So far, six lysophosphatidic acid receptors that respond to LPA have been discovered and categorized based on their homology. Despite the abundance of evidence relating LPA cellular activities to different pathological conditions, little is known about the involvement of LPA in the field of neuropsychiatric and neurodegenerative diseases. The purpose of this review is to define LPA activities related to the illnesses stated above in order to better understand these pathologies and provide future novel treatment strategies based on the latest data.